A Study to Evaluate the Effectiveness of a Structured Teaching Programme on Knowledge and Attitude Regarding Selected Comfort Measures Among Post-Caesarean Mothers - Chandrakala K.B.; Geetha D.; Veena Santhosh (International Journal of Midwifery Nursing And Practices, 2026)
Introduction: The study was conducted to assess the levels of knowledge and attitudes related to selected comfort measures among mothers who had undergone caesarean delivery, both before and after an intervention. It also aimed to identify any associations between these outcomes and certain demographic variables. Methods: A pre-experimental design using a single group with pretest and posttest measures was employed. The sample consisted of 100 post-caesarean mothers, chosen through a nonprobability convenience sampling method. Data were gathered using a demographic information form, a structured questionnaire to evaluate knowledge, and a Likert scale to assess attitudes. The data collected was analyzed using both descriptive and inferential statistical methods. Results: The structured teaching programme was effective in enhancing the participants’ knowledge and improving their attitudes toward selected comfort measures following caesarean delivery. The mean knowledge score increased from 12.77 in the pretest to 25.26 in the posttest, with a calculated t-value of 39.046 (p
Keywords: Knowledge; attitude; caesarean section; comfort measures; post-caesarean mothers; structured teaching programme